GAAP implementation guide - Bragg, Steven M. (John Wiley & Sons, 2004)
This essential guide offers clear advice on how accountants can convert a set of GAAP rules into an operational implementation, including related policies and procedures, controls, forms, and record keeping requirements. Each chapter contains definitions and concepts addressing the most common GAAP issues, and a decision tree for each accounting rule offers several alternatives available to the user.